The Juridical Analysis of the Granting of Building Use Rights on the Land of Management Rights - Cahyaningsih, Santi (Jurnal Konstatering, 2022)
The granting of Building Utilization Rights on the land of Tegal City Government Management Rights is carried out by making a contract agreement. The legal provisions regarding the implementation of the granting of Building Use Rights on land with Right of Management are appropriate and fair in carrying out the implementation of the transfer of the management rights of the Tegal City Government to prospective HPL holders by providing a certificate of Building Use Rights. This thesis research aims to identify and analyze the Pasar Sore House and Shop Development Agreement (RUKO) which was signed by the Tegal City Government as the holder of Management Rights with PT. Building Use over Management Rights. The research approach method used in this thesis is the legal research methodsociological juridical. Specifications using descriptive analysis. The type of data used in this study is primary data which includes: the 1945 Constitution of the Republic of Indonesia; BAL; Code of Civil law; Regulation of the Minister of Home Affairs; as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and study of documents or library materials. The data analysis method used in analyzing the data, namely qualitative analysis in this study, is to present and explain conclusions and solve problems related to the research titles that have been collected. The results of the research show that: The granting of Building Use Rights can occur on top of Management Rights due to a land use agreement between the two parties. Prospective building use rights holders can be drawn up with a notarial deed or private deed drawn up on the basis of an agreement between the management rights holder and the prospective HGB holder. The Tegal City Government as the main authority holder will not transfer assets to third parties because in essence the Management Right is State land which may not be traded to anyone.Keywords: Agreement; Building; Management.